Impact of Corporate Social Responsibility, Managerial and Institutional Ownership, on Financial Performance and Firm Value - Annisha Fitriana; Komala, Lenda (Santoso Academy Network, 2025)
This study aims to examine the impact of Corporate Social Responsibility (CSR), Managerial Ownership, and Institutional Ownership on Financial Performance and Firm Value within 10 food and beverage sub-sector Firms listed on the IDX from 2017 to 2021. The analysis employs Panel Data Analysis using the Eviews application. The findings reveal that both CSR and Managerial Ownership exert a significant positive influence on Financial Performance, while Institutional Ownership does not demonstrate a statistically significant effect. Conversely, Managerial Ownership negatively affects Firm Value, whereas CSR and Institutional Ownership show no significant impact on Firm Value. When analyzed together, the CSR Ratio, Managerial Ownership, and Institutional Ownership significantly affect both Financial Performance and Firm Value. This study enriches academic discourse by enhancing the understanding of how CSR, managerial ownership, and institutional ownership collectively influence financial performance and firm value. For practitioners, the insights provided can inform strategies for optimizing ownership structures and CSR initiatives to improve financial outcomes and market valuation. The managerial implication is that Firms should strategically incorporate CSR programs to foster sustainable social and economic value.